Structural and Physico-Chemical Changes of Mozzarella di Bufala Campana Cheese Influenced by Covering Liquid Composition - Irene Fenga; Marcello Alinovi; Maria Paciulli; Germano Mucchetti; Emma Chiavaro (Foods)
Mozzarella di Bufala Campana is an Italian protected designation of origin cheese characterized by a stretched structure, high moisture (<65%), and short shelf life (<30 days). This cheese is generally stored refrigerated in a covering liquid that is an aqueous solution containing NaCl and organic acids. Although microbial growth has been reported as the main cause of quality deterioration, physico-chemical phenomena (water/solute migration, enzymatic reactions, etc.) also play a role in determining the cheese quality and its storability. This study investigates the effect of covering liquids formulated with different percentages of NaCl (1, 2%) and types of organic acids (lactic acid, citric acid, and a 1:1 mix of both) on the evolution of some physico-chemical characteristics of the cheese (moisture, pH, electrical conductivity, color, expressible serum, texture, rheology) during a 30-day storage period. Eight cheese batches collected from different dairies were considered as replicates of the study. The % of NaCl in the covering liquid showed a strong, significant effect on the evolution of different structural, physico-chemical characteristics of the cheeses; in particular, a NaCl concentration of 2% caused the greatest extent of moisture content increase because of casein swelling during storage, accompanied by softening of the structure.